![\sqrt{x} ( \sqrt{x} + 1) = 6 \sqrt{x} ( \sqrt{x} + 1) = 6](https://tex.z-dn.net/?f=+%5Csqrt%7Bx%7D+%28+%5Csqrt%7Bx%7D++%2B+1%29+%3D+6)
Answers
Answered by
7
⭐⭐
Multiplying √x by both the terms,
x+√x = 6
x+√x -6 = 0
Make its factors, as we make in a quadratic equation
x+3-2
-6 = 0
[
+3]-2[
+3]
(-2)(
+3) = 0
Then each factor can be zero, so possible values of values can be given by:-
+3 = 0
= -3
x = 9
OR
-2 = 0
= 2
x = 4
Similar questions
Math,
7 months ago
Computer Science,
7 months ago
Sociology,
1 year ago
Sociology,
1 year ago
Political Science,
1 year ago